Screening and identification of a novel target specific for hepatoma cell line HepG2 from the FliTrx bacterial peptide library - Li, Wenhan; Lei, Ping; Yu, Bing; Wu, Sha; Peng, Jilin; Zhao, Xiaoping; Zhu, Huifen; Kirschfink, Michael; Shen, Guanxin (Acta biochimica et biophysica Sinica, 2008)
To explore new targets for hepatoma research, we used a surface display library to screen novel tumor cell-specific peptides. The bacterial FliTrx system was screened with living normal liver cell line L02 and hepatoma cell line HepG2 successively to search for hepatoma-specific peptides. Three clones (Hep1, Hep2, and Hep3) were identified to be specific to HepG2 compared with L02 and other cancer cell lines. Three-dimensional structural prediction proved that peptides inserted into the active site of Escherichia coli thioredoxin (TrxA) formed certain loop structures protruding out of the surface. Western blot analysis showed that FliC/TrxA-peptide fusion proteins could be directly used to detect HepG2 cells. Three different FliC/TrxA-peptide fusion proteins targeted the same molecule, at approximately 140 kDa, on HepG2 cells. This work presented for the first time the application of the FliTrx library in screening living cells. Three peptides were obtained that could be potential candidates for targeted liver cancer therapy.